Submandibular Gland Preservation during Concurrent Neck Dissection and Transoral Surgery for Oropharyngeal Squamous Cell Carcinoma. (April 2014) - Howard, Brittany E.; Hinni, Michael L.; Nagel, Thomas H.; Chang, Yu-Hui; Cheng, Meng-Ru; Hayden, Richard E.
Objectives: Analyze the effect of ipsilateral submandibular gland preservation on patients undergoing concurrent neck dissection and transoral surgery for oropharyngeal squamous cell carcinoma. Evaluate for (1) intraoperative and postoperative communications between the oropharynx and neck and (2) oncologic outcomes. Study Design: Retrospective chart review of prospectively collected data. Setting: Tertiary academic referral center. Methods and Subjects: Retrospective chart review of patients undergoing transoral laser resection of oropharyngeal squamous cell carcinoma with simultaneous neck dissection(s) for primary, persistent, recurrent, and second primary disease between January 1999 and February 2013. Data analyzed for operative technique, pathologic diagnosis, postoperative course, complications, and oncologic outcomes. Results: Overall 253 patients were identified. Of these, 96 patients underwent ipsilateral submandibular gland preservation and 157 underwent ipsilateral submandibular gland removal at the time of neck dissection. The prevalence of intraoperative communication between the neck and oropharynx was significantly lower in cases with submandibular gland preservation (2/96, 2.08%) compared to those with submandibular gland removal (22/157, 14.13%). No postoperative leaks occurred in the gland preservation group (0/96, 0%) compared to a leak prevalence of 8.92% (14/157) when the gland was removed ( P = .0041). There was no difference in local, regional, or distant disease recurrence between submandibular gland preservation and gland removal. Similarly, Kaplan-Meier analysis showed no difference in disease free survival, disease specific survival, or overall survival. Conclusions: Submandibular gland preservation during neck dissection in patients undergoing transoral surgery for oropharyngeal squamous cell carcinoma significantly reduces the risk of intraoperative and postoperative salivary leaks without compromising oncologic outcomes.